Peroxidase inactivation of commonly processed Philippines fruits by water-blanching - Ignacio, Marikit P. (1978)
The study was undertaken to establish optimum blanching schedules four commonly processed Philippine fruits, namely, carabao mango, lakatan banana, guayabano, and santol. The optimum blanching time was taken as that duration of heating which accomplished high reduction in enzyme activity without seriously impairing the sensory properties of the fruit. By correlation of results between peroxidase activity analysis and sensory evaluation, optimum blanching times at 212°F for the four fruits and their corresponding internal temperature range predicted on the basis of heat penetration studies are as follows: carabao mango, 5.66 minutes (179-185°F); lakatan banana, 5.33 minutes (175-185°F); guayabano, 6 minutes (147-150°F0; and santol, 4.99 minutes (155-170°F). Heat inactivation curves drawn for the four fruits indicated mango peroxidase as the most heat-resistant having obtained the highest D value equal to 9.5 minutes at 212°F, followed by peroxidase from santol (D=8.4), then from banana (D=5.9), and guayabano (D=5.6). Regeneration was detected in all the fruit samples blanched using actual 2D values, and stored at 0°F for two weeks. Extent of enzyme regeneration reached its highest at 19.73% for banana, followed by guayabano with 15.11%, then santol, 14.92% and mango, 4.09%. There appears to be no relationship between the heat resistance and ability of enzymes to regenerate under frozen storage conditions. Of the sensory properties, texture appeared to be the most critically affected by blanching, followed by flavor. Generally, as blanching time increased, improvement of color was observed due to inhibition of oxidizing enzymes causing enzymatic browning.